2019
DOI: 10.1126/scitranslmed.aan5662
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota influences skeletal muscle mass and function in mice

Abstract: The functional interactions between the gut microbiota and the host are important for host physiology, homeostasis, and sustained health. We compared the skeletal muscle of germ-free mice that lacked a gut microbiota to the skeletal muscle of pathogen-free mice that had a gut microbiota. Compared to pathogen-free mouse skeletal muscle, germ-free mouse skeletal muscle showed atrophy, decreased expression of insulin-like growth factor 1, and reduced transcription of genes associated with skeletal muscle growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
483
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(507 citation statements)
references
References 49 publications
(66 reference statements)
20
483
0
4
Order By: Relevance
“…Finally, when germ-free mice were transplanted with a fecal content of pathogen-free mice treated with antibiotics, they developed muscle atrophy and reduced function due to a reduced healthy microbiota. These data agreed with Manickam et al's study, which demonstrated dysbiosis in pathogen-free mice treated with the antibiotic metronidazole producing scarce gastrocnemius muscle mass, abnormal activation of atrophy genes, and insulin resistence [209]. Conversely, fecal transplantation of old human subjects with high physical performance, called high functioning, in germ-free mice induced a peculiar microflora rich in Prevotella and Barnesiella species and developed more grip strength [210].…”
Section: The Emerging Concept Of the Gut-muscle Axis-role Of Exercisesupporting
confidence: 90%
“…Finally, when germ-free mice were transplanted with a fecal content of pathogen-free mice treated with antibiotics, they developed muscle atrophy and reduced function due to a reduced healthy microbiota. These data agreed with Manickam et al's study, which demonstrated dysbiosis in pathogen-free mice treated with the antibiotic metronidazole producing scarce gastrocnemius muscle mass, abnormal activation of atrophy genes, and insulin resistence [209]. Conversely, fecal transplantation of old human subjects with high physical performance, called high functioning, in germ-free mice induced a peculiar microflora rich in Prevotella and Barnesiella species and developed more grip strength [210].…”
Section: The Emerging Concept Of the Gut-muscle Axis-role Of Exercisesupporting
confidence: 90%
“…Since cancer-induced cytokines/chemokines as well as cancer treatments can affect the gut microbiome, it will be interesting to determine an association between the gut microbiome and muscle dysfunction in breast cancer patients. Consistent with this possibility, animals that lack a microbiota in gut have reduced muscle weight, reduced transcription of genes in mitochondria, and reduced neurotransmitter for neuromuscular junction [181]. Since breast cancer is not a single disease and broadly classified into five subtypes [182,183], how each subtype affects skeletal muscle function is unknown.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…In other words, gut bacteria could control host body weight in that study. In addition, gut microbiota play a role in maintaining appropriate amount of skeletal muscles and their function in mice (12). Furthermore, Bradley et al discovered that gut microbes increase interferon α/β signals of host lung stromal cells, thereby improving the ability of these cells to resist influenza virus infection (13).…”
Section: Introductionmentioning
confidence: 99%